Diagnosis of the perception that users have about the quality of products and services provided by BanEcuador B.P. branch Tulcán. - Pérez Andrade, Martha (SATHIRI, 2020)
Experiences and evaluations make customers not only decide where to request the products and services offered by a financial institution, but also they are guided by the quality of the service provided; customers have always demanded good treatment, attention, reliability, quality, reasonable times, appropriate processes, accessibility and constant innovation by the entity and public officials, therefore, each of the institutions have been faced with the challenge of looking for different alternatives to enrich these demands and be able to attract new customers, this study sought to identify whether the perception of satisfaction that users have regarding the quality of the products and services that grants BanEcuador BP influences its permanence inthe Financial Institution, carrying out a study with a quantitative approach, of descriptive-non exploratory type; we worked with a stratified sample composed of 186 clients of the Tulcán branch in 2018; for the data collection, a structured questionnaire was designed with 22 questions with a Likert scale, the result allowed us to know that the satisfaction of the client residing in the Tulcán canton when using the products and services provided by the Institution is 62.9% , highlighting the actions related to the advice by the staff of the Institution, while the attribute that needs to be improved is a greater communication about access to virtual banking and how this electronic channel can provide solutions in less time.
Keywords: Public Banking; Quality; perception; Financial Products and Services